Performance improvement of the mini hexagonal tube heat sink using nanofluids - Sriharan, G.; Harikrishnan, S.; Öztop, Hakan Fehmi (Elsevier Ltd, 2022)
The experimental investigation is accomplished to determine the improved performance of the mini hexagonal tube heat sink (MHTHS) using nanofluids (NFs). The three different NFs are prepared via a two-step method in which, Al2O3, MgO, and CuO nanoparticles with 0.1 vol fraction (VF) are dispersed into deionized water (DIW), individually. The experiment is conducted in the MHTHS under the following conditions. The volume flow rate (VFR) of DIW in the mini passage side (MPS) is maintained at 30 L per hour (lph), and the VFR of NFs in the hexagonal tube side (HTS) is varied from 10 lph to 50 lph. MgO-DIW NFs show the highest performance at 0.1 VF for 50 lph of HTS flow. Similarly, for 0.1 VF of Al2O3-DIW and CuO-DIW NFs, higher performance was achieved at 45lph of HTS flow. From the experimental data, the enhancement of the convective heat transfer coefficient (CHTC) of MgO-DIW, Al2O3-DIW, and CuO-DIW NFs are reported as 40%, 28%, and 22%, respectively. However, the augmentation of the overall heat transfer coefficient of MgO-DIW, Al2O3-DIW, and CuO-DIW NFs are 32 %, 24%, and 16%, respectively. Furthermore, the overall Effectiveness of MHTHS is enhanced by about 42% using MgO-DIW nanofluid. Hence, MgO-DIW NF could be used efficiently to cool the hexagonal-shaped miniature devices. © 2022 Elsevier Ltd
Keywords: Effectiveness; Heat transfer coefficient; Hexagonal tube; Mini passage; Nanofluids; Thermal conductivity; Viscosity